Desentralisasi: Harapan dan Tantangan bagi Dunia Pendidikan - Ahdurrahmansyah Ahdurrahmansyah (Millah: Journal of Religious Studies, 2001)
Decentralization is an issue often discussed by many people. It becomes a discourse moved to balance the hegemony of centralist concept that deeply rooted in Indonesia. The application of decentralization and autonomy program has many impacts on many aspects including the education decentralization. The education decentralization gives many hopes and challenges. It is expected that the education decentralization could solve the education problems faced up to now. But it is a challenge for the regional government because of the real condition of region doesn't always have good potential that can easily be improved. In that context, this writing will study of the autonomy correlated with the education decentralization. The study will be arranged specifically to the key question of what the form of education decentralization is and what the hopes and challenges of education decentralization are.